Helminth parasites of Ctenosciaena gracilicirrhus (Perciformes: Sciaenidae) from the coast of Angra dos Reis, Rio de Janeiro State, Brazil - Melissa Q. Cárdenas; Berenice M. M. Fernandes; Márcia C.N. Justo; Antonia L. dos Santos; Simone C. Cohen (Revista Mexicana de Biodiversidad)
During a survey of the helminth parasites of Ctenosciaena gracilicirrrhus from the Atlantic Ocean, off Angra dos Reis, Rio de Janeiro.